2017
DOI: 10.1158/2326-6066.cir-16-0297
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells

Abstract: Myeloid cells evolutionary developed as a major mechanism to protect the host. They evolved as a critical barrier against infections and are important contributors to tissue remodeling. However, in cancer, myeloid cells are largely converted to serve a new master – tumor cells. This process is epitomized by myeloid-derived suppressor cells (MDSC). These cells are closely related to neutrophils and monocytes. MDSC are not present at steady state in healthy individuals and appear in cancer and pathological condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
1,377
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,470 publications
(1,417 citation statements)
references
References 79 publications
28
1,377
2
10
Order By: Relevance
“…Among them, tumor recruitment and localization of MDSCs represent one major impediment to effective antitumor immune responses. MDSCs can be subdivided into two groups: M-MDSCs, which are phenotypically and morphologically comparable to monocytes, and PMN-MDSCs, which are comparable to neutrophils (58,59). Once they accumulate at the tumor site, MDSCs exert a suppressive role on immune cells, mainly on T cells, via several immune-suppressive factors, including arginase-1, iNOS, TGF-β, IL-10, and ROS, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, tumor recruitment and localization of MDSCs represent one major impediment to effective antitumor immune responses. MDSCs can be subdivided into two groups: M-MDSCs, which are phenotypically and morphologically comparable to monocytes, and PMN-MDSCs, which are comparable to neutrophils (58,59). Once they accumulate at the tumor site, MDSCs exert a suppressive role on immune cells, mainly on T cells, via several immune-suppressive factors, including arginase-1, iNOS, TGF-β, IL-10, and ROS, among others.…”
Section: Discussionmentioning
confidence: 99%
“…MDSC exercise their immunosuppressive activities through various mechanisms, including the generation of high levels of inducible nitric oxide (iNOS, mainly M-MDSC) and reactive oxygen species (ROS, mainly PMN-MDSC) that induce the nitration of the T-cell receptor and prevent its interaction with cognate antigen-major histocompatibility complex (MHC) [8], as well as by the production of arginase-1 that in combination with high levels of iNOS restricts the availability of the amino acid L-arginine, which is essential for T-cell proliferation [9]. It has been suggested that the usage of each mechanism may depend on the specific MDSC subset and the site of immunosuppression [10].…”
Section: Cd15mentioning
confidence: 99%
“…[myeloid-derived suppressor cells (MDSCs)] accumulate in the blood, spleen, lymph nodes, bone marrow, and tumor microenvironments in tumor-bearing animals and cancer patients (4)(5)(6)(7)(8). These cells, as well as CD11b þ Gr1 -tissue resident macrophages, inhibit innate and adaptive immunity, thereby promoting tumor immune escape (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Gr1mentioning
confidence: 99%
“…These cells, as well as CD11b þ Gr1 -tissue resident macrophages, inhibit innate and adaptive immunity, thereby promoting tumor immune escape (1)(2)(3)(4)(5)(6)(7)(8). These immunosuppressive cells inhibit maturation of antigen-presenting dendritic cells (DCs), suppress T-cell activation and NK-cell cytotoxicity and induce regulatory T-cell (Treg) development, leading to dysfunctional cell-mediated antitumor immunity through the release of immunosuppressive factors such as IL10, TGFb1, IL6, VEGF, and ROS (9)(10).…”
Section: Gr1mentioning
confidence: 99%